002: UNDERSTANDING AND PREVENTING BIAS IN PUBLIC PRIVATE PARTNERSHIPS. (24th August 2015) - Beaudreault, Amy R; Shlisky, Julie D; Mclean, Mireille S
Abstract : Background: Bias in science is unavoidable; however, with decreasing funding the need for public-private partnerships (PPPs) is at a high. PPPs provide diverse institutions an opportunity to increase capacity, expertise, and outreach often times not feasible by independent engagement. Many institutions offer varying documents on how to minimize conflict of interest but the methodology used in their development is limited. Objectives: The goal of this research was to examine neutrality in nutrition science from an organizational perspective, looking at expert testimonials and recommendations, utilizing qualitative methods. Methods: The Sackler Institute for Nutrition Science conducted 17 in-depth interviews in 2014 with nutrition researchers. A purposeful sample was employed, using a criterion-based frame of diverse demographic variables. Interviewees were selected for their range in nutrition experience, nationality, age, gender, sector, and country of employment. Researchers developed a 16-item interview guide that was reviewed by a panel of experts (n=2) and pilot-tested (n=2) to obtain validity. The interview guide was divided into three categories of questions: neutrality definition; personal experiences; and, recommendations. The researchers analyzed data using inductive content analysis. This process used open coding, constructing categories, and abstraction of reoccurring or insightful words, phrases, and sentences. Data segments related to professional experiences, perceptions of neutrality, and recommendations on how to ensure neutrality were aggregated based on commonalities. Result: Findings include that bias is inherent and disclosure and balance are essential in PPPs. Conclusion: Recommendations include development of institution-wide policies that pay attention to the competing interests commonly found in nutrition science. Disclosures should be robust and include not only financial conflicts but professional and personal; the disclosures should be publicly available.